Pressure effects on nanostructure development of ABC triblock copolymers. (5th August 2016) - Cho, Junhan
Abstract: The development of nanoscale morphologies for a molten compressible polymeric surfactant is investigated by using a recently formulated self-consistent field theory. A linear ABC block copolymer is taken as our model system that allows a disparity in the propensities for curved interfaces and in pressure responses of ij-pairs. The interplay of those features leads the copolymer to new morphologies at a moderate segregation level and at ambient condition such as B-shell/C-core networks with tetrapod connections and packed cylinders in a 2-dimensional array. It is shown that pressure is an effective means of morphology control and identification. Upon pressurization of B-shell domains, the former structures reveal P23 symmetry. The packed cylinders are shown to possess centered rectangular C2mm symmetry. The C2mm cylinders and P23 structures are considered to turn up by disparity in the densities of block domains and effective reduction in packing frustration. Graphical abstract: Highlights: Morphology development for a molten compressible ABC block copolymer is to be investigated via self-consistent field theory. There emerge new mesophases such as the networked morphology of P23 space group and the packed cylinders of C2mm space group. C2mm and P23 structures stabilize through the variation of block density disparity and the reduced packing frustration.